Effectiveness of honey-lidocaine and honey-povidone iodine combination cream therapy in healing second-degree perineal rupture wounds - Yuni, Sitti Nurmarati; Farid, Imam Ahmadi; Irianta, Trika; Madya, Fatmawati; Sunarno, Isharyah; Farid, Monika Fitria; Lotisna, David (Journal of Neonatal Surgery, 2025)
Background: Second-degree perineal rupture involves vaginal mucosa and perineal muscle injury, influenced by factors like primiparity, macrosomia, and prolonged labor. Wound healing follows stages of hemostasis, inflammation, proliferation, and remodeling. To accelerate the wound healing, honey has been used as an alternative due to its antimicrobial, anti-inflammatory, and antioxidant properties. This study evaluates the effectiveness of honey-lidocaine and honey-povidone iodine combinations in healing perineal wound. Methods: A double-blind RCT was conducted at Siti Khadijah 1 Hospital (Feb–Aug 2024), involving postpartum women with second-degree perineal rupture. Participants applied one of three creams twice a day for 14 days. Healing was assessed using the REEDA scale on days 0, 1, 7, and 14. The data were analyzed using ANOVA, Kruskal-Wallis, Mann-Whitney, paired T-tests, and Wilcoxon tests (p < 0.05). Results: Most participants with normal BMI were nulliparous, aged 20–35. By day 7, REEDA scores were significantly lower (p < 0.001) in the honey-lidocaine group. The best healing was observed by day 14. Conclusions: Honey-lidocaine cream demonstrates faster healing than honey-povidone iodine and placebo, offering a promising postpartum wound care option